Fabrication of cellulose aerogel from sugarcane bagasse as drug delivery carriers - Chin, Sukfun; Jimmy, Fiona Beragai; Pang, Suhcem (Universiti Sains Malaysia, 2016)
Currently most of the aerogel-based drug delivery carriers are made from non-biodegradable materials, such as silica. In this study, highly porous cellulose aerogels with Brunauer-Emmett-Teller (BET) surface areas that varied between 22 m2 g-1 and 525 m2 g-1 were prepared from a sugarcane bagasse cellulose solution of various concentrations. The potential utility of cellulose aerogels as controlled release carriers was evaluated by loading methylene blue (MB) as a model hydrophilic drug. The MB loading capacity and release kinetic profiles of cellulose aerogels were observed to be substantially influenced by their BET surface areas. Under optimum conditions, a maximum loading capacity of 6.4 mg MB mg-1 cellulose aerogel was achieved with sustained release of MB from cellulose aerogels at physiological pH over a period of 23 h